Pathological changes in the carp exposed to iron sulphate - Yuksel, H.; Ural, M.; Dorucu, M.; Karadas, E. (My University, 2006)
Histopathological changes in the carp exposed to iron sulphate were studied. Fish were exposed to iron sulphate solution at the concentrations of 0.9, 5 and 10 mg/L. Hyperplasia and degeneration of the gill lamellae, diffuse lymphocyte infiltration on the heart muscle, glia cell proliferation in the brain, hydropic degeneration of the liver of the fish were observed in carp exposed to 5 and 10 mg/L iron sulphate.
Keywords: Cyprinus carpio